Analysis of Proteins of Mouse Sarcoma Pseudotype Viruses: Type-Specific Radioimmunoassays for Ecotropic Virus p30's - Kennel, Stephen J. (J Virol, 1979)
Murine sarcoma virus pseudotypes were prepared by infection of nonproducer cells (A1-2), which were transformed by the Gazdar strain of mouse sarcoma virus, with Gross (N-tropic), WN1802B (B-tropic), or Moloney (NB-tropic) viruses. The respective host range pseudotype sarcoma viruses were defined by the titration characteristics on cells with the appropriate Fv-1 genotype. Proteins from virus progeny were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Bands present in both the 65,000- and the 10,000- to 20,000- molecular-weight regions of the gel distinguished the pseudotype viruses from their respective helpers. Furthermore, two protein bands were noted in the p30 region of murine sarcoma virus (Gross), one corresponding to Gross virus p30, and another of slightly slower mobility. However, since the mobility of the putative sarcoma p30 is nearly indentical to that of WN1802B, its presence could not be established by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Type-specific radioimmunoassays for Gross virus p30 and for WN1802B p30 were applied for analysis of pseudotype preparations, and among several ecotropic viruses tested, only the homologous virus scored in the respective assay. By use of these assays, pseudotype viruses were found to contain only 8 to 48% helper-specific p30's; the remainder is presumably derived from the sarcoma virus. IMAGES: